2017
DOI: 10.24248/eahrj.v1i1.385
|View full text |Cite
|
Sign up to set email alerts
|

Gridlock from Diagnosis to Treatment of Multidrug-Resistant Tuberculosis (MDR-TB) in Tanzania: Illuminating Potential Factors for Possible Intervention

Abstract: Characterise multidrug-resistant tuberculosis (MDR-TB)-treated cases during the scaling up of molecular diagnostics using Xpert MTB/RIF and GenoType MTBDRplus Design: Retrospective cohort study Results: A total of 223 MDR-TB patients were referred to the Kibong'oto Infectious Disease Hospital from January 2013 through December 2014. Four cities-Dar es Salaam, Mbeya, Mwanza, and Tanga-contributed 144 (65%) of referrals. Of the total referred patients, HIV coinfection was found in 92 (41%) and 180 (81%) had hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…4 This sobering fact has been illuminated in Tanzanian research studies that uncovered a health system gridlock largely contributed by limited resources and skills-training for front-line healthcare providers, and weak linkage to other health services with the subsequent effect of underuse of technologies. [5][6][7][8][9] Likewise, the prevalence of dual communicable and NCD epidemics is increasing, yet communicable clinics are unprepared to deal with dual services. 10 11 For instance, the prevalence of diabetes mellitus (DM) ranged 4%-17% and hypertension ranged 7%-25% in people leaving with HIV attending clinics in Tanzania cities, while, in other settings within Tanzania, the prevalence of DM ranged 4%-5% and hypertension ranged 22%-30%.…”
Section: Introductionmentioning
confidence: 99%
“…4 This sobering fact has been illuminated in Tanzanian research studies that uncovered a health system gridlock largely contributed by limited resources and skills-training for front-line healthcare providers, and weak linkage to other health services with the subsequent effect of underuse of technologies. [5][6][7][8][9] Likewise, the prevalence of dual communicable and NCD epidemics is increasing, yet communicable clinics are unprepared to deal with dual services. 10 11 For instance, the prevalence of diabetes mellitus (DM) ranged 4%-17% and hypertension ranged 7%-25% in people leaving with HIV attending clinics in Tanzania cities, while, in other settings within Tanzania, the prevalence of DM ranged 4%-5% and hypertension ranged 22%-30%.…”
Section: Introductionmentioning
confidence: 99%
“…At the health centre level, the median (IQR) individuals with TB diagnosed in the year 2020 at the intervention facilities was 330 (42-524) and control facilities was 330 (38-557) (p = 0.29), whereas the median (IQR) individuals with DM attending the services in the same time period was 160 (0-757) in intervention facilities and 60 (0-1598) control health centres (p = 0.89). Individuals were more often identified with dual TB and DM at the intervention hospitals with a median of eight (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) individuals per facility compared with a median of one individual per control facility 1 (0-3) (p = 0.02). The same trend was observed in health centres; dual TB and DM was diagnosed in a median of four individuals (4-5) per facility in intervention facilities compared to none at any of the control facilities (p = 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Such recommendations and guidelines also suggest the benefit of integrating services for NCDs with TB and HIV care, but this has not been accomplished in Tanzania [11]. For instance, the introduction of molecular diagnostics for multidrug resistant (MDR)-TB in Tanzania did not translate into a reduction of mortality as described elsewhere [12], prompting a nationwide examination of barriers and bottlenecks [13]. Importantly, this examination found that most of the front-line health care providers in TB and HIV clinics did not regularly receive continuous on-the-job medical education and therefore lacked updated knowledge and skills on the international standards of TB care.…”
Section: Introductionmentioning
confidence: 99%